(3efJNHGJ ef cJGH GdchGcH GdeVjFI aj GdPjd Ydi JGQjN GHf NWjH GdfGUQjIs - (3eLghds; (3YdGA GdOjf CHh GdMSf,J (B843 (3g` s
(3ChdgG (B:s
(3SfI EKfi YTQI hCQHYeGFI Jhai YHO GdQMef Gdabjg GdHZOGOi hai JGQjN GHf NdcGf Cfg Ydj Hf YHO GdhGMO GdHZOGOi GdeYQha HUQjY GdOdG s
(3BNQgG (B:s
(3hGNJGQ eMdg GdYbHI aHfi OhQg ajgG hgj CTQa fhGMi MdH hCaVdgG GfJgi hdjcf gPG BNQ eG ENJQJ fbdg ef JGQjN GdchGcH GdeVjFI hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3GdhQb eVWQH GdJQJjHs
(3JHUQI GdYfhGf (B:s
(3oefJNHs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs